The Cell-Penetrating Peptide Tat Facilitates Effective Internalization of PSD-95 Inhibitors Into Blood–Brain Barrier Endothelial Cells but less Efficient Permeation Across the Blood–Brain Barrier In Vitro and In Vivo - Al Humaidan, Emma Lisa; Pedersen, Sidse Lund; Burkhart, Annette; Rasmussen, Charlotte Laurfelt Munch; Moos, Torben; Fuchs, Peter; Fernandes, Eduardo Filipe Alves; Ozgür, Burak; Strømgaard, Kristian; Bach, Anders; Brodin, Birger; Kristensen, Mie (Frontiers in Drug Delivery, 2022)
Inhibition of the interaction between the scaffolding protein PSD-95 and the NMDA receptor has been shown to obstruct ischemic stroke-triggered excitotoxic reactions leading to neuronal death. The peptides NR2B9c and N-dimer are inhibitors of this interaction. Delivery of the peptides to the brain is challenging due to the general low blood-brain barrier (BBB) permeability. NR2B9c and N-dimer have therefore been conjugated to the cell-penetrating peptide (CPP) Tat, to facilitate BBB permeation. However, the BBB permeation of Tat-NR2B9c and Tat-N-dimer has not been fully elucidated. We recently demonstrated that the BBB permeation in vitro and in vivo was lowered upon conjugation of NR2B9c or N-dimer to Tat. In the present study, we aimed to further understand the impact of cargo conjugation to Tat with respect to interaction with -and permeation across the BBB in vitro and in vivo. The peptides were labelled with the fluorophore TAMRA (T) and demonstrated efficient Tat-mediated uptake into BBB endothelial cells, but differed in their degree of plasma membrane interaction -and embedding (T-Tat-NR2B9c = T-Tat > T-Tat-N-dimer) as well as in their chemical stability (T-Tat-N-dimer = T-Tat > T-Tat-NR2B9c). The Tat-conjugates all displayed a similar degree of self-association and/or plasma protein adsorption. T-Tat-NR2B9c and T-Tat affected the BBB integrity, but not the permeation of the paracellular marker C14-mannitol. T-Tat-NR2B9c and T-Tat-N-dimer displayed less efficient permeation across an in vitro model representing the healthy BBB, when compared to T-Tat, and low BBB permeation in healthy rats